Effect of calcium additives on physicochemical aspects of cell wall pectin and sensory attributes of canned peach - Vasilakakis, Miltiadis; Diamantidis, Grigorios; Mignani, Ilaria; Manganaris, George A. (My University, 2005)
Quality evaluation of calcium-treated processed peaches was determined by physical, chemical and sensory analyses. Textural and structural properties of canned peaches indicated that calcium-treated peaches gained better firmness retention and greater proportion of uronic acids between the insoluble and water-soluble pectin fraction than untreated peaches, probably because of higher cell wall calcium content. However, a direct relationship cannot be established between calcium and uronic acid content in pectin fractions. A range of sensory descriptors assessed by a trained panel provided results that challenge accepted interpretations in the field of quality evaluation. The results indicated the possibility of processing high quality calcium-treated canned peaches with acceptable qualitative features. Calcium lactate is suggested as a potential calcium source in the peach canning industry, since it provided both better textural features and sensory attributes. The interactions among calcium, the physicochemical properties of the cell wall framework and sensory attributes are discussed.
Keywords: Calcium; Peach; Pectin; Cell wall; Firmness; Sensory analysis; Canning process